(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Hypertension is a risk factor for cardiovascular disease and premature mortality worldwide. Effective management of this condition requires the integration of structured interventions, such as disease management programs, which have proven clinically significant in increasing treatment adherence and improving patient outcomes. Objective To evaluate the effectiveness of a disease management program in achieving target blood pressure in primary care. Materials and methods A retrospective random sampling method was used to include 200 medical cards (form 025/u) of patients with arterial hypertension registered for dispensary care in 4 city polyclinics of Astana, Kazakhstan, for 2023-2024. Patients were divided into two groups depending on whether they achieved the target BP level (<140/90 mmHg). Clinical and laboratory parameters, including age, lipid profile, glucose level, and systolic/diastolic BP, were analyzed. The completeness of the disease management program implementation was also assessed using a criterion scale. Results Of the total number of patients, 170 (85%) successfully achieved the target blood pressure level, and 30 (15%) did not. Individuals with uncontrolled arterial hypertension were characterized by a significantly higher mean age (71.17 ± 10.87 vs. 66.08 ± 10.14 years; p < 0.05) and elevated levels of low-density lipoprotein cholesterol (LDL-C) (4.86 ± 1.75 vs. 3.53 ± 1.32 mmol/L; p < 0.05). Mean systolic and diastolic BP were also significantly higher in this group (142.83 ± 12.98/87.00 ± 5.63 mmHg vs 133.34 ± 12.41/82.43 ± 6.80 mmHg; p < 0.05). Full compliance with the Disease Management Program was associated with good clinical outcomes, with the group that achieved target blood pressure levels and fully complied with the program scoring significantly higher on the program implementation scores (8.2 ± 0.7 vs 5.6 ± 1.1; p < 0.001). Conclusion Full implementation of the disease management program significantly improves lipid profile and BP control in the primary care. The study also demonstrated the importance of regular follow-up, patient monitoring, and lifestyle interventions as key components of effective hypertension management. BJMS, Vol. 24 No. 04 October’25 Page : 1181-1188